Anomalies of the anaerobic tricarboxylic acid cycle in Shewanella oneidensis revealed by Tn-seq - Brutinel, Evan D.; Gralnick, Jeffrey A. (Molecular microbiology, 2012)
Summary The availability of increasingly inexpensive sequencing combined with an ever‐expanding molecular biology toolbox has transported classical bacterial genetics into the 21st century. Whole genome genetic fitness analysis using transposon mutagenesis combined with next‐generation high‐throughput sequencing (Tn‐seq) promises to revolutionize systems level analysis of microbial metabolism. Tn‐seq measures the frequency of actual members of a heterogeneous mutant pool undergoing purifying selection to determine the contribution of every non‐essential gene in the genome to the fitness of an organism under a given condition. Here we use Tn‐seq to assess gene function in the Gram negative γ‐proteobacterium Shewanella oneidensis strain MR‐1. In addition to being a model environmental organism, there is considerable interest in using S. oneidensis as a platform organism for bioremediation and biotechnology, necessitating a complete understanding of the metabolic pathways that may be utilized. Our analysis reveals unique aspects of S. oneidensis metabolism overlooked by over 30 years of classical genetic and systems level analysis. We report the utilization of an alternative citrate synthase and describe a dynamic branching of the S. oneidensis anaerobic tricarboxylic acid cycle, unreported in any other organism, which may be a widespread strategy for microbes adept at dissipating reducing equivalents via anaerobic respiration.